Réponses

2014-02-22T22:58:48+01:00
Bonsoir

C = 12 : (-4 + 5) - 4x7
   = 12 : 1 - 28
   = 12 - 28
   = -16

D = 4 - 4x(-4 + 5 x 2) + 4 - 4
   = 4 - 4 x (-4 + 10) + 0
   = 4 - 4 x 6
   = 4 - 24
   = -20

E =  -3 - [ 7 - 2x( -3 + 13)]
   = -3 - (7 - 2 x 10)
   = -3 - (7 - 20)
   = -3 - (-13)
   = -3 + 13
   = 10

S =  -8 - ( -4 + 5 - 7) + ( -2 + 9)
   = -8 - (-6) + 7
   = 8 + 6 + 7
   = 21

E =  (7 - 5) + (2 - 3) - (-7 + 5 - 3)
   = 2 + (-1) - (-5)
   = 2 - 1 + 5
   = 6
pour le D je me suis tromper c'est: 4-4x(-4+5x2)+4x4-4
D = 4 - 4 x (-4 + 5 x 2) + 4 x 4 - 4
D = 4 - 4 x (-4 + 10) + 16 - 4
D = 4 - 4 x 6 + 16 - 4
D = 4 - 24 + 16 - 4
D = -8